2012
DOI: 10.1109/tgrs.2011.2170695
|View full text |Cite
|
Sign up to set email alerts
|

Global Analysis of EnviSat Burst Echoes Over Inland Water

Abstract: Satellite radar altimeters have an established and increasingly vital role in monitoring the Earth's surface inland water resources. This paper analyzes two years of EnviSat burst echoes (which have 3.9-m nominal along-track separation) over rivers, lakes, and ephemeral water globally to assess the increase in monitoring potential afforded by the higher pulse repetition frequency (PRF) of the next generation of synthetic aperture radar altimeters and investigate spatial burst correlation. Burst echoes at 1800 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Global analysis of these 'individual echoes' (IEs) has revealed that even small pools of water can be identified, and height timeseries successfully retrieved from as few as 7 IEs [8]. As a further illustration of this, Figure 4 shows a timeseries generated from 3 years of Burst Echo data over the Uele River compared with the corresponding 18Hz timeseries.…”
Section: Inland Water Target Analysismentioning
confidence: 96%
“…Global analysis of these 'individual echoes' (IEs) has revealed that even small pools of water can be identified, and height timeseries successfully retrieved from as few as 7 IEs [8]. As a further illustration of this, Figure 4 shows a timeseries generated from 3 years of Burst Echo data over the Uele River compared with the corresponding 18Hz timeseries.…”
Section: Inland Water Target Analysismentioning
confidence: 96%